AN EXPERIENCE OF SUPINE PCNL ON BILATERAL STAGHORN AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE - Zulfiqqar, Andy; Soeroharjo, Indrawarman (Indonesian Urological Association, 2020)
Objective: The aim of this article was to reports our experiences PCNL on ADPKD patients. Case(s) Presentation: We report the case of a 38-year-old male with autosomal dominant polycystic kidney disease associated with bilateral staghorn diseases. We performed a supine PCNL on left kidney. Discussion: ADPKD may arise sporadically, the developmental abnormality that resulting in multiple cysts, hypertension, hematuria, polyuria, plank pain, and are prone to reccurent urinary tract infection and renal stones. ADPKD is one most commonly genetics disorder than frequently results in End Stage Renal Disease (ESRD). Population of ADPKD has a higher risk to have a nephrolithiasis, thus it may hastened the onset of ESRD. Open surgeries was one of treatment of choices of ADPKD with staghorn stones, but considering of high rates of morbidity. Recently there’s consistent switching the trend on minimal invasive treatment such as ESWL and PCNL. Conclusion: PCNL may considered as an effective and safe procedure in managing nephrolithiasis in ADPKD, further studies with larger sample and longer periods observation is needed to confirmed role of PCNL in preserving kidney on ADPKD with staghorn kidney.